2005
DOI: 10.1007/s00216-005-3255-8
|View full text |Cite
|
Sign up to set email alerts
|

Optical interrogation of molecularly imprinted polymers and development of MIP sensors: a review

Abstract: This article reviews the progress and developments achieved in the past five years (2000-2005) in the application of optical analytical techniques to the evaluation of molecularly imprinted polymer (MIP) characteristics. The MIP binding efficiency, recognition processes and selectivity have been intensively studied by optical means due to the general high sensitivity and simplicity of the utilisation of optical techniques. In addition, recent progress in the covalent linkage of MIPs to optical transducers has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(81 citation statements)
references
References 76 publications
0
77
0
4
Order By: Relevance
“…In addition, the weak peaks at 1638.28 and 1638.71 cm -1 were the stretching vibrations of C=C, indicating that most of the functional monomer (MAA) and the crosslinkers (EGDMA) had the cross-linking reaction. 32 Consequently, the results suggested that the MIPs and NIPs were successfully synthesized.…”
Section: Characterization Studies Of Qds-mip and Qds-nipmentioning
confidence: 98%
“…In addition, the weak peaks at 1638.28 and 1638.71 cm -1 were the stretching vibrations of C=C, indicating that most of the functional monomer (MAA) and the crosslinkers (EGDMA) had the cross-linking reaction. 32 Consequently, the results suggested that the MIPs and NIPs were successfully synthesized.…”
Section: Characterization Studies Of Qds-mip and Qds-nipmentioning
confidence: 98%
“…The fluorescence response of the systems was shown to be related to the concentration of template and importantly that this response was stereoselective. recent progress in the covalent linkage of MIPs to optical transducers has allowed for the realisation of highly efficient and robust optical MIP-based molecular recognition sensors (Henry et al, 2005). Most of the strategies involve in the design and use of fluorescent ligands and fluorotag-ligand conjugates in the preparation of the fluorescent sensors.…”
Section: Optical Sensorsmentioning
confidence: 99%
“…29,38,138 Sempre dentro da química supramolecular, o desenvolvimento do conceito de bibliotecas combinatórias virtuais por meio da química combinatória dinâmica 139 representa uma ferramenta bastante útil, pela geração de diversidade (virtual) de receptores e de espécies formadas pela interação não covalente de receptores com unidades de sinalização. Também a técnica de impressões moleculares (molecular imprinting) pode ser usada na moldagem de receptores poliméricos, adequados para os mais diferentes analitos, 140 apresentando potencial para a obtenção de novos quimiossensores.…”
Section: Perspectivasunclassified